Belajar Melalui Video di Media Sosial Dapat Meningkatkan Keterampilan Pemasangan Kateter pada Mahasiswa Keperawatan (Journal of Telenursing (JOTING), 2019)
The purpose of this study was to analyze the use of video on social media as a learning medium for catheter placement skills in nursing students. The research design is a quasi-experimental design with pretest-posttest with group control. The results showed that there were differences in the average score of catheter placement skills in the intervention group before being given a video and 32.27 installation of a SOP catheter, after being given a video and SOP catheter placement being 72.73. Statistical test results of independent sample t-test obtained p value of 0,000 (p Î± Î± 0.05). Conclusion, there is an influence of the use of video on social media on catheter placement skills in nursing students.Keywords: Catheter, Learning Media, Video